2019
DOI: 10.1051/matecconf/201927703013
|View full text |Cite
|
Sign up to set email alerts
|

A review of causes of variation order in the construction of terrace housing projects in Malaysia

Abstract: Variation order refers to any changes from the scope, plan, specification or contract document in the construction project. This changes of work is a common problem in construction projects in Malaysia. It is inevitable in any construction project and this problem can become more serious when variation order causes work progress to be impaired as a results it increased the construction time and cost that affects the construction industry in Malaysia. This paper critically review the causes of variation order i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…In Malaysia, reviewed the causes of variation and found that client-related variations are the most dominant causes of variations in construction [30]. The review reported 18 prominent causes of variation and they are; change of scope by client, owner's financial problems, inadequate project objectives, replacement of materials or procedures, impediment to prompt decision-making process, obstinate nature of the owner, change in specifications by the owner, change in design by the consultant, errors and omissions in design, conflicts among contract documents, technology changes, value engineering, lack of coordination, design complexity, inadequate working drawing details, consultants' lack of required data, poor knowledge of available materials and equipment, and ambiguous design details.…”
Section: Causes Of Variations On Construction Projectsmentioning
confidence: 99%
“…In Malaysia, reviewed the causes of variation and found that client-related variations are the most dominant causes of variations in construction [30]. The review reported 18 prominent causes of variation and they are; change of scope by client, owner's financial problems, inadequate project objectives, replacement of materials or procedures, impediment to prompt decision-making process, obstinate nature of the owner, change in specifications by the owner, change in design by the consultant, errors and omissions in design, conflicts among contract documents, technology changes, value engineering, lack of coordination, design complexity, inadequate working drawing details, consultants' lack of required data, poor knowledge of available materials and equipment, and ambiguous design details.…”
Section: Causes Of Variations On Construction Projectsmentioning
confidence: 99%
“…There are different reasons for variation orders that were identified in different studies, such as: Change in scope (Arain, Assaf, & Pheng, 2004), Owner financial problems (Clough, Sears, Sears, Segner, & Rounds, 2015;O'Brien, 1998), Obstructing the decision-making process (Sanvido, Grobler, Parfitt, Guvenis, & Coyle, 1992;Gray & Hughes, 2007), Lack of flexibility of the owner (Arain et al, 2004;Wang, 2000), The owner change the specifications (O'Brien, 1998), The consultant's change in design (Fisk & Reynolds, 1988), Complexity of the design (Arain et al, 2004), Inadequate details of working drawings (Arain et al, 2004), causing variations in the project, Insufficient design (Fisk & Reynolds, 1988;Force, 1990). Mohammad, Ani, and Rakmat (2017) investigated the main effects of variation orders on projects and suggested that the effects are: the increase of project time, the increase in the project cost, the delay of logistics, the impact on the quality of the project, and the destruction and reconstruction of certain components. Moreover, variation orders have a direct impact on labor productivity whether it is individual, or group works.…”
Section: Variation Ordersmentioning
confidence: 99%
“…Eltahir et al [6] distinguished significant ten agents that cause change orders in the Sudani building project. The variation orders cause and their effect on the Iraqi construction projects, then interpreted the causes using data mining techniques [28,29]. More of the previous studies have examined the variation orders causes as independent causes.…”
Section: Previous Studiesmentioning
confidence: 99%